The Potential And Surveillance Studies Alumnus Faculty Of Economics And Business Islam UIN Raden Intan Lampung - Hanif, Hanif (Universitas Muhammadiyah Prof. DR HAMKA., 2019)
Alumni searches (Tracer study) as part of an alumni network construction should be done regularly and scheduled. The alumni FEBI can generally be absorbed in the world of work with a waiting period of normal working ranges of less than 3 (three) months and the majority of alumni working in the field of employment in accordance with their competence. Based on the results of the questionnaire tracer study, the majority of graduates in response to their competence as a result of the learning process in Febi, pretty good. Alumni also commented that soft skill competencies they have higher than hard skills and competencies it has in accordance with the needs of the working world are increasingly demanding mastery of soft skills